2021
DOI: 10.3389/fimmu.2021.727959
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Deprivation Disturbs Immune Surveillance and Promotes the Progression of Hepatocellular Carcinoma

Abstract: Sleep disturbance is common in patients with cancer and is associated with poor prognosis. However, the effects of sleep deprivation (SD) on immune surveillance during the development of hepatocellular carcinoma (HC) and the underlying mechanisms are not known. This was investigated in the present study using mouse models of SD and tumorigenesis. We determined that acute and chronic sleep deprivation (CSD) altered the relative proportions of various immune cell types in blood and peripheral organs. CSD increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…However, millions of people across the world are sleep-deprived because of sleep-related disorders, lifestyle choices, and so on [ 1 , 2 ]. Sleep disturbances can cause a wide range of disorders throughout the body and lead to increased mortality and morbidity from cardiovascular diseases, cancer, depression, and a series of neurodegenerative diseases [ 3 – 5 ]. Importantly, emerging evidence has demonstrated that cognitive dysfunction is one of the most common and serious consequences induced by sleep loss.…”
Section: Introductionmentioning
confidence: 99%
“…However, millions of people across the world are sleep-deprived because of sleep-related disorders, lifestyle choices, and so on [ 1 , 2 ]. Sleep disturbances can cause a wide range of disorders throughout the body and lead to increased mortality and morbidity from cardiovascular diseases, cancer, depression, and a series of neurodegenerative diseases [ 3 – 5 ]. Importantly, emerging evidence has demonstrated that cognitive dysfunction is one of the most common and serious consequences induced by sleep loss.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, multiple studies have found that sleep quality is related to tumor progression, and our previous studies have shown that sleep disorders can impair immunity and promote tumor growth through immune cells in blood and peripheral immune organs in a mouse hepatocellular carcinoma model; however, there is a lack of research in clinical patients with liver cancer [ 18 , 19 ]. This study focuses on two types of patients with HBV cirrhosis and non-HBV cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor cells can down regulate ligands recognized by NK cell receptors through metalloproteinase mediated cleavage and other mechanisms, leading to immune escape ( 40 , 41 ). Second, during tumor development, tumor cells and factors in the tumor microenvironment release a variety of immunosuppressive factors to escape immune surveillance by NK cells ( 42 ). Third, NK cells are inhibited by immunosuppressive cells after immune escape of tumor cells ( 43 ).…”
Section: Nk Cellsmentioning
confidence: 99%